Diagnosis of Bladder Cancer with Urinary Cytology, Immunocytology and DNA-Image-Cytometry1 - Bernhard Planz; Christian Synek; Thomas Deix; Alfred Böcking; Michael Marberger (Analytical Cellular Pathology)
DNA‐image‐cytometry and antibodies directed against the Lewis X‐ and the 486p 3/12 antigen were applied to improve diagnostic accuracy of urinary cytology for the detection of bladder cancer. Cytology, immunocytology and DNA‐image‐cytometry were performed in spontaneously voided urine samples and barbotage bladder washings from 71 patients. The DNA content was determined using the CM‐1 Cytometer according to the recommendation of the ESCAP Consensus Report on Standardization of DNA‐image‐cytometry (1995). For immunocytological examination we used the monoclonal anti Lewis X antibody P‐12 and antibody 486p 3/12. All patients underwent subsequent cystoscopy and for any suspicious lesion biopsy or transurethral resection was done. Histological findings revealed 31 patients with transitional cell carcinomas of different stages and grades of malignancy. 40 patients had various benign diseases of the urinary bladder. Cytology yielded a sensitivity of 68% and a specificity of 100%. DNA aneuploidy was detected in 81% of cancer patients with a specificity of 100%. By combination of these two methods the overall sensitivity increased to 87%. Immunocytology with Lewis X and 486p 3/12 antibodies showed reactivity in 84% and 87% in combination with a specificity of 80% and 70%, respectively. By combining urinary cytology, immunocytology and/or DNA‐image‐cytometry the overall sensitivity increased to 94% with no change in specificity. DNA‐image‐cytometry should be used to evaluate particularly urothelial cells suspicious for malignancy in urinary specimens. Because of low specificity the monoclonal antibodies against Lewis X‐ and 486p 3/12 antigens are not helpful in screening for bladder cancer. Nevertheless, their high sensitivity may justify their use in case DNA image cytometry is not available and in the follow up of patients with transitional cell carcinoma.